2022
DOI: 10.1111/aas.14090
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for an individual patient data meta‐analysis on blood pressure targets after cardiac arrest

Abstract: Background: Hypotension is common after cardiac arrest (CA), and current guidelines recommend using vasopressors to target mean arterial blood pressure (MAP) higher than 65 mmHg. Pilot trials have compared higher and lower MAP targets. We will review the evidence on whether higher MAP improves outcome after cardiac arrest.Methods: This systematic review and meta-analysis will be conducted based on a systematic search of relevant major medical databases from their inception onwards,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…12 A systematic review and meta-analysis with individual patient data identified four randomized clinical trials and a total of 1087 patients with varying MAP targets (65-75 mmHg vs. 80-100 mmHg). 13,14 The meta-analysis could not exclude a clinically significant treatment effect on mortality (<25% relative risk) of a higher or lower MAP-target using frequentist statistics.…”
Section: Introductionmentioning
confidence: 99%
“…12 A systematic review and meta-analysis with individual patient data identified four randomized clinical trials and a total of 1087 patients with varying MAP targets (65-75 mmHg vs. 80-100 mmHg). 13,14 The meta-analysis could not exclude a clinically significant treatment effect on mortality (<25% relative risk) of a higher or lower MAP-target using frequentist statistics.…”
Section: Introductionmentioning
confidence: 99%